The relationship between mental toughness, anxiety with the achievement motivation adolescent badminton athlete - Zafira, Nadila; Ditya Candra, Adiska Rani (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: Mental and emotional problems in badminton are the main focus in the effort to improve athlete performance. In this study there are several problems that occur in teenage athletes PB Flash, especially related to the level mental toughness, anxiety and achievement motivation athlete badminton. Purpose: This study identifies levels of mental toughness, anxiety and achievement motivation in teenage badminton in PB Flash in Serang regency. Methods: This research uses correlation quantitative descriptive methods with purposive sampling techniques. The sample consisted of 11 athletes aged 15-20 years. The tool used in this research is a questionnaire through a google form. The questionnaire shared are SMTQ (Sport Mental Toughness), SCAT (Sport Competition Anxiety Test) and SMS-28 (Sport Motive Scale). Descriptive analysis and double linear regression test, which are used to analyze data. Results: Based on the results obtained, the data is be concluded it is possible to perform a correlation test with a significance value of 0.020 with such a result there is a low significant relationship between the three variables. Level of mental toughness with a medium category of 7 athletes (63.7%), 4 with a high category (36.6%), a level anxiety low of 2 athletes (18.1%), a medium level 7 athlete (63.7%) and a high level of anxiety for 2 (18.1%), while the achievement motivation with an average category of 8 at the medium category (72.7%) and 3 at the high level (27.3%). Conclusion: The level of mental toughness, anxiety and achievement motivation athlete teenagers PB. Flash Serang has not strong enough relationship. As mental toughness increases, achievement motivation increases, and whereas anxiety increases then achievement motivation decreases experienced by athletes The results of this study also suggested that coaches and PB Flash Serang players should be able to add a mental training program for athletes.